y=-12z2

Rewrite the equation as -12z2=y.

-12z2=y

Multiply both sides of the equation by -2.

-2⋅(-12)⋅z2=-2⋅y

Cancel the common factor of 2.

Move the leading negative in -12 into the numerator.

-2⋅-12⋅z2=-2⋅y

Factor 2 out of -2.

2(-1)⋅-12⋅z2=-2⋅y

Cancel the common factor.

2⋅-1⋅-12⋅z2=-2⋅y

Rewrite the expression.

-1⋅-1⋅z2=-2⋅y

-1⋅-1⋅z2=-2⋅y

Multiply.

Multiply -1 by -1.

1⋅z2=-2⋅y

Multiply z2 by 1.

z2=-2⋅y

z2=-2⋅y

z2=-2y

Take the square root of both sides of the equation to eliminate the exponent on the left side.

z=±-2y

First, use the positive value of the ± to find the first solution.

z=-2y

Next, use the negative value of the ± to find the second solution.

z=–2y

The complete solution is the result of both the positive and negative portions of the solution.

z=-2y

z=–2y

z=-2y

z=–2y

Solve for z y=-1/2z^2